The effect of insulin-induced hypoglycemia on inflammatory markers: A systematic review - Drummond, Juliana B.; Barbosa, Izabela G.; Dantzer, Robert; Teixeira, Antonio L. (Brain, behavior, and immunity, 2018)
•Acute hypoglycaemia induces a pro-inflammatory state.•Elevation of inflammatory markers occurs in both type-1 and non-diabetic subjects.•Activation of the sympathetic nervous system is a likely mediator of these effects. The effects of acute hypoglycemia on markers of inflammation have been investigated, but the results have been heterogeneous. We aimed to perform a systematic review about the acute effects of insulin-induced hypoglycemia on inflammatory markers in patients with diabetes as well as non-diabetic subjects. A systematic search of the literature using the electronic databases MEDLINE and SCOPUS was conducted through September 2017. Search terms included: “hypoglycemia”,“ insulin”, “cytokines”, and “inflammation”. We included original studies assessing peripheral inflammatory markers during insulin-induced hypoglycemia in humans. Two hundred twenty-two citations were initially retrieved. Eleven studies were included in our systematic review. Acute hypoglycemia increases total leukocyte number and several pro-inflammatory markers. Elevation in pro-inflammatory markers in response to insulin-induced acute hypoglycemia appears to be of similar magnitude in non-diabetic subjects and in type-1 diabetic patients with intact awareness of hypoglycemia. Adrenaline rises in response to acute hypoglycemia correlates with the increase of pro-inflammatory markers. Acute hypoglycemia induces a pro-inflammatory state in both type-1 diabetic and non-diabetic subjects with no apparent significant difference between these two populations. Activation of the sympathetic nervous system is a likely mediator of these effects.